Subduction dynamics and structural controls on shear wave splitting along the South American convergent margin. (December 2020) - Lynner, Colton; Beck, Susan L.
Abstract: Observations of shear wave splitting have provided constraints on patterns of deformation in the mantle in a variety of tectonic settings, including those with complex dynamics such as subduction zones. The South American subduction system is characterized by the longest laterally continuous subducting slab present today. As such, it represents an excellent natural laboratory to study variability in anisotropy along thousands of kilometers of a subduction zone. We perform shear wave splitting analyses at 59 stations along the Chilean coast spanning over 2500 km of the subducting Nazca slab. This dataset specifically targets stations that sample minimal amounts of thickened South American crust and mantle wedge material making it easier to attribute splitting to the sub-slab mantle. We observe a stark transition in splitting from the central Bolivian Orocline to southern Chile indicative of a transition in mantle deformation beneath the subducting slab from convergent flow beneath the Orocline to trench parallel flow farther south. This supports previous conceptual models of mantle dynamics in the region where a stagnation point exists beneath the Bolivian Orocline resulting in plate motion driven flow with trench parallel escape flow to both the north and south. Our results as well as previous measurements largely agree with a recent numerical modeling study that has proposed similar large-scale deformation patterns as well as local deviations due to slab structures like tears. The agreement between model predictions and our observations, however, is not universal along strike. We see several regions where measured splitting deviates significantly from predictions. These areas warrant further study and will aid in refining future geodynamic modeling efforts. Highlights: Shear wave splitting at Chilean coastal seismic stations. Change in sub-slab mantle dynamics along strike. Trench normal splitting beneath the Bolivian Orocline and trench parallel.flow in central Chile